English Teachers’ Challenges and Strategies in Teaching Deaf Students in Bengkulu City - Felisia, Renata Artha; Kasmaini, Kasmaini; Sukesi, Erni (UNIB Press, 2025)
English teachers can have unique challenges in teaching English to deaf students. They need to utilize special strategies and resources. Gaining insight about the teachers’ challenges and strategies in teaching English for deaf students is important to enhance English language education for deaf learners. This research is intended to find the challenges of English teachers in teaching deaf students, besides to find out the strategies practiced by English teachers to overcome the challenges. The design was a qualitative research design. The data for this study were obtained from classroom observations and interviews conducted in-depth with two English teachers from two special schools (SLBN) located in Bengkulu City. The instruments were an observation sheet and an interview guidance. The results also show that teachers faced various challenges, including adapting the teaching material, encountering communication barriers and maintaining the motivation of the students. They used visual aids, interactive media, clear nonverbal communication, and student-centered approaches to overcome these challenges. The study also highlighted that resource limitation and the variety of sign language systems impacted the effectiveness of teaching. Deaf students face great challenges and English teachers use a wide range of effective strategies to overcome them. The outcome underscores the value of visual, interactive and relational pedagogies. It is important to better understand these issues in other contexts and with a greater diversity of disability.